Riders’ food safety knowledge and practices: do they comply - Noor Azmi, Ain Fatihin; Abdullah, Norhidayah; Saad, Mazni; Turgarini, Dewi; Mat Yusoff, Norhayati (Human Resource Management Academic Research Society, 2022)
The food service industry has evolved recently to cope with global changes and demands. Food riders have been recruited to keep the food business significant in an area with food safety concerns in mind. Although food riders don't need to take food safety and hygiene courses, undoubtedly it is their responsibility to prevent foodborne disease outbreaks. Therefore, this study was initiated to identify food safety knowledge, attitudes and practices (KAP) among 84 food riders in Shah Alam using a quantitative correlational study (Pearson Correlation Coefficient) while the mediating effect was investigated using the Hayes PROCESS. The results showed that the attitude of the food rider mediates the relationship between knowledge and practice of food safety. Research findings from 84 respondents, consisting of men (82.1%), and women (17.9%). Their ages ranged from 18 to 27 years (64.3%). In addition, 70 people (83.3%) of them have higher education, at the diploma, master, and PhD levels. There is a fact that 98.8% of them have less than three years of working experience as food riders. The results revealed that there is a significant relationship between all attributes tested (p<0.05) as well as it is proven that attitudes partially mediate the relationship between knowledge and practices. This study may help in developing food safety education intervention programs for food riders in improving their food safety knowledge, attitude and practice.